Teacher Strategies in Improving Communication Skills in Children at PAUD YPJ Tembagapura - Apriyansyah, Chandra; Hasugian, Deborawati; Priyanti, Nita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to describe the implementation of the Inquiry Learning model in improving early childhood communication skills at PAUD YPJ Tembagapura, an institution with multilingual and multicultural characteristics. The research problem arises from the teachers’ challenge in fostering active interaction among children with diverse linguistic backgrounds. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observations, and documentation involving teachers, principals, and parents. Thematic analysis was applied to identify communication strategies and patterns of language development among children. The findings reveal that Inquiry Learning plays a crucial role in fostering children’s active, critical, and collaborative communication. Stimulating questions and exploratory activities enhance children’s curiosity, while the use of concrete media and the natural environment strengthens verbal engagement. Teachers act as active facilitators who guide children to speak, listen, and respond to peers’ ideas confidently. Inclusive strategies also help quiet children participate actively in classroom discussions. Overall, the Inquiry Learning model effectively builds children’s confidence and communication skills, making it a relevant pedagogical approach for multicultural early childhood education settings in Indonesia.